2023
DOI: 10.1088/1674-1056/ac8cdf
|View full text |Cite
|
Sign up to set email alerts
|

A color image encryption algorithm based on hyperchaotic map and DNA mutation

Abstract: Combining hyperchaotic map, cross-plane operation and gene theory, a color image encryption scheme is devised. First, the hyperchaotic map used in the encryption scheme is analyzed and studied. On the basis of the dynamics of hyperchaotic map, a color image encryption scheme is designed. At the end of the encryption process, a DNA mutation operation is used to increase the encoding images’ randomness and improve the encryption algorithm’s security. Finally, simulation experiments, performance analysis, and att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 49 publications
(47 reference statements)
0
20
0
Order By: Relevance
“…Specially, when q = 1, the system is of integer-order and the dynamical behaviors with parameter b 1 are shown in figure 6. It is shown that the FOCCS is periodic state when b 1 ä [5,15], and shows mainly a chaotic state in b 1 ä (6,15) , where b 1 ä (8.56, 8.71) and (10.8, 11.01) are the periodic windows. Comparing figure 5 and figure 6 shows that the fractional-order has higher LEs and chaos of the bifurcation diagram is more obvious compared to the integer-order.…”
Section: Dynamical Behaviors Analysis With Parameters and Ordermentioning
confidence: 97%
See 1 more Smart Citation
“…Specially, when q = 1, the system is of integer-order and the dynamical behaviors with parameter b 1 are shown in figure 6. It is shown that the FOCCS is periodic state when b 1 ä [5,15], and shows mainly a chaotic state in b 1 ä (6,15) , where b 1 ä (8.56, 8.71) and (10.8, 11.01) are the periodic windows. Comparing figure 5 and figure 6 shows that the fractional-order has higher LEs and chaos of the bifurcation diagram is more obvious compared to the integer-order.…”
Section: Dynamical Behaviors Analysis With Parameters and Ordermentioning
confidence: 97%
“…Yao et al [12] introduce fractional-order into FHN neural circuits and investigated fractional-order neural circuits composed of fractional-order basic components. Due to the good performance of chaos, it is nowadays widely used in information security and other applications such as encryption and secure communication [13][14][15][16][17].The most important thing for fractional-order systems is the solution method. To solve fractional-order differential equations, various algorithms have been proposed [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the chaotic maps gradually become a hot research topic due to easy implementation, low cost and high complexity. In addition, they have broad application prospects in cryptography, [1,2] image encryption, [3,4] pseudorandom sequences generation, [5,6] secure communication [7,8] and other fields. [9][10][11] However, many existing chaotic maps still have limitations such as small keyspace, multiple periodic windows and weak ergodicity.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, it had a lot of essential applications in image encryption, security, and other engineering fields. [2][3][4][5][6][7][8] In the past few decades, researchers have been exploring the chaos that can produce complex dynamical behavior, and it is worth mentioning that multi-scroll attractors and coexisting attractors have become a hot topic in nonlinear research. [9][10][11][12][13][14][15][16][17][18][19] The state variable can go through multiple orbital states and jump randomly in different transitions for the multi-scroll attractors.…”
Section: Introductionmentioning
confidence: 99%